Attention and its Functions in the Life and Activities of the Person - Razykova L.T; Razykova Lola Tuychievna (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
attention in the life and activity of a person performs many different functions. The author of the article turned his attention to the organic basis, which is the structures of the brain, undoubtedly ensuring the functioning of attention.